Six Sigma Approach to Enhance Concurrency of the Procurement Process for Raw Materials - Kochov, Atanas (Array, 2021)
This paper presents the improvement of the procurement process for raw materials in a real manufacturing company supported by the Lean Sig Sigma as structured approach to deliver the improvement. The manufacturing company that is a subject of this paper have received a significant amount of complains regarding the internal purchase orders approval process and the overall procurement process of the company from both internal employees and external vendors and contractors. Considering that the company is procuring the raw goods from selected vendors, therefore the entire manufacturing plan depends on these materials, the company decided to improve this process trough Lean Six Sigma. The Lean Six Sigma approach was selected in order to obtain the improvement in a short time, based on indicators that were previously analyzed and prioritized. The paper focuses on simplifying of the process trough decreasing the number of mandatory steps.